Pendampingan Sertifikasi Halal Pada UMKM Kopi Arabika Distrik Walelagama Papua Pegunungan: indonesia - Syarifah, Syarifah; Ahmad, Ahmad; Haluk, Elroy (UII, 2025)
This Community Service (PKM) aims to increase awareness and understanding of MSME actors regarding the importance of halal certification and provide solutions to problems faced by Arabica Coffee MSME actors through halal certification assistance. The methods used in this activity are socialization, assistance, and evaluation. The solution to the problems faced is that non-seasonal entrepreneurs who sell halal products can apply for halal certificates on the condition that they submit a halal supervisor who is Muslim, ensure that the production process is in accordance with Islamic law, separate the tools and materials used for halal and non-halal products. The results of the activity show that the community service activity has been carried out well and has a positive impact on the community as evidenced by a very significant figure of 33% to 81% in the level of increasing community understanding regarding the Indonesian Ulema Council, benefits, impacts, and issuance of Halal Certification. The supporting factor for this activity is the active participation of the community in activities from start to finish and the inhibiting factor in this activity is the unstable communication network so that it is difficult to communicate to determine the schedule.